UPAYA MENINGKATKAN KINERJA GURU DALAM MENETAPKAN KRITERIA KETUNASAN MINIMAL MELALUI WORKSHOP DI LUBUKLINGGAU - fahrunrosi fahrunrosi (LP4MK STKIP PGRI Lubuklinggau, 2021)
School action research with problem formulation What are the efforts to improve the ability of teachers in setting Minimum Completeness Criteria (KKM)? and whether through the workshop can improve the ability of teachers in setting Minimum Completeness Criteria (KKM) subject teachers. The purpose of this research is to increase the ability of teachers in determining the Minimum Completeness Criteria (KKM) for subjects. The results of this study are expected to be useful and provide a learning experience for teachers, because through the workshop teachers are given materials and exercises to determine the Minimum Completeness Criteria (KKM) according to their subjects. And subject teachers can have the ability to set Minimum Completeness Criteria so that the teaching and learning process is better. 40 teachers were involved in the research through this workshop. The research design is cyclical, consisting of 4 stages, namely planning, implementation, observation, and reflection. From the analysis, it is found that there is an increase in teacher readiness and performance in determining minimum completeness criteria from cycle I to cycle II. The achievement of performance indicators is found in the second cycle of action. Therefore, it can be concluded that through workshops can improve teacher performance in setting minimum completeness criteria in Lubuklinggau. Thus, it can be suggested to supervisors or other researchers that workshop activities can be used as an alternative in improving teacher performance in setting minimum completeness criteria.